2022
DOI: 10.1108/ijlss-08-2021-0141
|View full text |Cite
|
Sign up to set email alerts
|

Importance of first-line employees in lean implementation in SMEs: a systematic literature review

Abstract: Purpose Existing research evidence shows a fragmented understanding of the roles of first-line employees (FLEs) as essential factors for successful lean implementation in small- and medium-sized enterprises (SMEs), provoking recent calls for additional research on the identification of enablers and barriers for lean acceptance among workers. Therefore, this paper aims to identify related enablers and barriers to lean implementation among FLEs and determine future research avenues for improving the understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 192 publications
1
6
0
Order By: Relevance
“…The findings may result from the nature of Nigerian manufacturing SMEs in manufacturing mostly consumable items and less advanced products, as posited by (the Bank of Industry, 2018). The findings also relate to the study of (Knapic et al, 2022;Uluskan et al, 2018). H8 shows that employee relations positively and significantly affect the change commitment dimension of organizational readiness for change.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The findings may result from the nature of Nigerian manufacturing SMEs in manufacturing mostly consumable items and less advanced products, as posited by (the Bank of Industry, 2018). The findings also relate to the study of (Knapic et al, 2022;Uluskan et al, 2018). H8 shows that employee relations positively and significantly affect the change commitment dimension of organizational readiness for change.…”
Section: Discussionmentioning
confidence: 56%
“…Employee relations refer to employees' participation in improving quality and performance (Uluskan et al, 2018). It involves employees' responsibility for the quality, feedback on their quality performance, involvement in quality decisions, and reward for superior quality that can enhance employees' readiness for change to Lean (Knapic et al, 2022). It is apparent from the studies on Lean readiness that the role played by employees is very significant to the successful deployment of Lean in manufacturing firms.…”
Section: Employee Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such lack of resources has made it a necessity for small businesses to adopt lean initiatives within their business processes to minimize waste, improve quality and deliver value to the customer. Studies have shown that the role of leadership/top management and employee relations are pivotal to the actualization of effective process management that can be geared towards delivering value to the customer and removal of any non-adding value activities, which is the fundamental principle of lean philosophy (Knapic et al, 2022;Nagamani Subramanian & Suresh, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a need for SMEs to deploy lean initiatives within their business to eradicate waste, improve quality, reduce Therefore, in order to successfully implement lean initiatives and reduce implementation failure, the study intends to investigate the level of readiness for lean implementation among Nigerian manufacturing SMEs, with a focus on leadership/top management, employee relations, process management, and customer relations. (Knapic et al, 2022;Prasad et al, 2023;Shafiq & Soratana, 2020). Based on the recommendations of scholars on the need for future studies regarding lean to be conducted in developing countries with an emphasis on leadership/ top management and employee relations Rodgers et al, 2021).…”
Section: Introductionmentioning
confidence: 99%